The rise of Clostridium difficile infection in lung transplant recipients in the modern era. (14th January 2013) - Lee, Janet T.; Hertz, Marshall I.; Dunitz, Jordan M.; Kelly, Rosemary F.; D'Cunha, Jonathan; Whitson, Bryan A.; Shumway, Sara J.
Abstract: Purpose: Clostridium difficile infection (CDI) rates have been rising in recent years. We aimed to characterize CDI in lung transplant recipients in the modern era and hypothesized that CDI would increase the mortality risk. Methods: We performed a retrospective chart review of patients undergoing transplantation at our center from 1/2006 to 7/2011. Attributes of CDI+ and CDI− groups were compared using Student's t ‐ and chi‐square tests (α = 0.05). Multivariate Cox proportional hazard models were used to control for confounding factors. Results: Overall CDI incidence was 22.5%. Seven of 151 patients (4.6%) developed CDI during the initial hospitalization after transplantation (mean time 10.6 ± 6 d) while 27 patients (19.7%) developed CDI after discharge (mean time 467 ± 471 d). Incidence rate was 224.6 cases/100 000 patient‐days compared to 110 cases/100 000 patient‐days (rate for entire hospital). CDI was not predictive of mortality (HR 2.06, 95% CI 0.94–4.52). Conclusion: CDI rates in lung transplant recipients are high in the modern era. No risk factors for CDI were identified. Although not statistically significant, CDI+ patients had a higher risk of death. The economic burden of CDI and trend toward worse outcomes for CDI patients have important implications for post‐operative surveillance of CDI‐related complications and need for CDI prophylaxis.